Indonesian Frozen and Processed Crab Export Performance and Competitiveness Analysis - Uswatun Khasanah; Wen-Chi Huang; Rosihan Asmara (Socio-Economics/Agribusiness Department, 2019)
This paper aimed to analyze the performance and competitiveness of Indonesian crabs in the international market by comparing it with other major crab export countries (China, Philippines, Vietnam and Korea). Two crab products were included in the study, namely processed crabs in cans (HS 160510) and frozen crabs (HS 030614). The Trade Balance Index (TBI), Normalized Revealed Comparative Advantage (NRCA), and the Comparative Export Index (CEP) were used by analyzing data from the Central Statistics Agency (BPS), Ministry of Maritime Affairs and Fisheries (KKP) in Indonesia as well as from UN COMTRADE, and Trade Map. The results based on TBI that the processed crabs were at the maturity stage, while the frozen crabs were at the growth stage. Only processed crab products had CEP values above 1, which means Indonesia is specialized and more competitive in processed crab products.